Fatigue safety factor of a transonic centrifugal compressor impeller subject to blade thickness - Kabalyk, Kirill; Bednarz, Arkadiusz; Kantyka, Krzysztof (Scientific reports, 2025)
This sensitivity study is focused on understanding the rate at which blade thickness can affect the risk of high-cycle fatigue failure in an impeller of a centrifugal compressor. The investigated Ti-alloy impeller serves to compress and deliver feed air into the combustion chamber of the jet-engine commercially known as DGEN 380. The risk of blade resonance at take-off exists between the tangential eigenmode with four nodal diameters and the fourth engine-order excitation source. The study uses weak coupling of the fluid- and structural numerical solvers to simulate the resonant vibrations of three impeller designs with lower, baseline and higher blade thickness. The transient aerodynamic pressure load is first estimated with the use of harmonic balance Fourier-transformation method. The load is afterwards applied to the structural harmonic-response model and the vibratory stresses are computed for a series of critical damping ratios. The following assessment of safety factors is done based on the Haigh diagram built-up with the use of Goodman equation. The requirement of minimally cycles to failure is applied to ensure that the blades sustain the resonance for a reasonably long period. The results indicate no potential high-cycle fatigue issues in baseline- and thicker designs. Safe operation of the thinner design is strongly affected by the system damping and its sustainable operation could not be guaranteed. The findings of the study should be useful to mechanical engineers solving the coupled fluid-structural problems in aerospace-, power- and environmental sectors.